The interaction effects of firm and partner tenure on audit quality / Josep Garcia-Blandon, Josep Maria Argiles-Bosch - Josep, Garcia-Blandon.
This paper investigates the impact of firm and partner tenure on audit quality, where audit quality is proxied by discretionary accruals. We study a sample of Spanish listed companies between 2005 and 2011 and address both the individual and the interaction effects of firm and partner tenure. Our study is motivated by the current debate, particularly intense at the EU level, on the impact of the auditor rotation regime on the quality of auditing. We find that, without considering the interaction effects, firm and partner tenure do not seem to play a relevant role as determinants of audit quality. Importantly, the interaction of firm and partner tenure shows stronger effects on audit quality than both forms of tenure separately considered. Finally, our analysis suggests that audit quality is maximized when medium firm and partner tenures interact. However, results for the interaction variables are sensitive to the accruals estimation method.